The Role of Brand Authenticity in Building Consumer Loyalty Toward Islamic Brands: A Literature Review - Berry Dhiyashavana; Ayulita Ramadhani; Haryaji Catur Putera Hasman (Yayasan Azhar Amanaa Yogyakarta, 2026)
This article examines the role of brand authenticity in building consumer loyalty toward Islamic brands. The study responds to the growing use of halal labels, Islamic symbols, and religious narratives in marketing, where consumers increasingly evaluate whether brand claims are consistent with actual practices. A narrative literature review was conducted by synthesizing peer-reviewed international and national journal articles on brand authenticity, Islamic branding, brand trust, perceived value, repurchase intention, and consumer loyalty. The review shows that brand authenticity strengthens loyalty through four interrelated dimensions: continuity, credibility, integrity, and symbolism. In Islamic brands, these dimensions are reflected in consistent halal identity, credible halal claims, ethical and transparent business conduct, and the ability of the brand to represent consumers' religious and social values. The synthesis also indicates that brand trust and perceived value are important mechanisms that connect authenticity with loyalty. Consumers are more likely to repurchase, recommend, and defend Islamic brands when they perceive the brands as honest, value-consistent, and able to deliver functional, emotional, social, and spiritual benefits. This article proposes a conceptual framework in which brand authenticity influences consumer loyalty both directly and through brand trust and perceived value, while religiosity and halal awareness may strengthen the relationship. The review contributes to Islamic marketing literature by integrating brand authenticity theory with Islamic branding and offers practical implications for managers of halal-oriented brands.